KINERJA REKSA DANA SYARIAH DAN KONVENSIONAL: APLIKASI MODEL JENSEN - Djaddang, Syahril; Susilawati, Susilawati (LPPM Universitas Terbuka, 2016)
The objective of this research is to evaluate the balanced shariah mutual fund performance compared with the balanced conventional mutual fund performance during the bull market of 2010-2012. Mutual fund performance can be measured by using Jensen Index, Sharpe Index, Treynor Index, MM Index, and TT Index. The information about security selection and market timing ability can be measured by using Henriksson-Merton Model and Treynor-Mazuy Model. The statistic methods used are Mixed Method to test hypothesis are one sample t-test, independent sample t-test, simple regression analysis, and multiple regression analysis. Finally, the results show that the conventional mutual funds have been able to outperform the shariah mutual funds. This underperform of shariah mutual fund performance can be happened because portofolio managers do not have superiority skills in security selection and market timing and also the differences of each mutual fund attributes. Based on the investigation of the data that is ot significant it indicates implication that investors and potential investors have the option to switch between these shariah mutual funds  and  conventional mutual funds depending on the market conditions and their personal preferences. Tujuan dari penelitian ini adalah untuk mengevaluasi syariah kinerja reksa dana dibandingkan dengan kinerja reksa dana konvensional yang seimbang dari 2010-2012. Kinerja reksa dana dapat diukur dengan menggunakan Jensen Index, Sharpe Index, Treynor Index, MM Index, dan TT Index. Informasi tentang pilihan keamanan dan kemampuan market timing dapat diukur dengan menggunakan Henriksson-Merton Model dan Treynor-Mazuy Model. Metode statistik yang digunakan adalah mix model untuk menguji hipotesis adalah salah satu sample t-test, sample t-test independent, analisis regresi sederhana, dan analisis regresi berganda. Akhirnya, hasil menunjukkan bahwa reksa dana konvensional telah mampu mengungguli syariah reksa dana. underperform ini kinerja reksa dana syariah dapat terjadi karena manajer portofolio tidak memiliki keterampilan keunggulan dalam seleksi keamanan dan timing pasar dan juga perbedaan atribut masing-masing reksa dana. Berdasarkan penyelidikan data yang ot signifikan ini menunjukkan implikasi bahwa investor dan calon investor memiliki pilihan untuk beralih antara reksa dana syariah ini dan reksa dana konvensional tergantung pada kondisi pasar dan preferensi pribadi mereka.